Digital palaeography: New machines and old texts (Dagstuhl seminar 14302) - Hassner, T; Sablatnig, R; Stutzmann, D; Tarte, S (Schloss Dagstuhl - Leibniz-Zentrum für Informatik, 2014)
This report documents the program and the outcomes of Dagstuhl Seminar 14302 "Digital Palaeography: New Machines and Old Texts", which focused on the nteraction of Palaeography and computerized tools developed in Computer Vision for the analysis of digital images. This seminar intertwined research reports from the most advanced teams in the field and interdisciplinary discussions on the potentials and limitations of future research and the establishment of a community of practice in Digital Palaeography. It resulted in new research directions in the Computer Sciences and new research strategies in Palaeography and in a better understanding of how to conduct interdisciplinary research across all the fields of expertise involved in Digital Palaeography.